Calculations of total electron-impact ionization cross sections for Fluoroketone C5F10O and Fluoronitrile C4F7N using modified Deutsch–Märk formula. (10th October 2017) - Xiong, Jiayu; Li, Xingwen; Wu, Jian; Guo, Xiaoxue; Zhao, Hu
Abstract: Both fluoroketone C5 F10 O and fluoronitrile C4 F7 N are promising substitute gases for SF6 . The electron-impact ionization cross sections for these two gases are calculated using the Deutsch–Märk (DM) formula and its modified method. The necessary molecular geometry optimization and electron population were determined by ab initio calculation, which was performed with quantum chemistry code. The level of calculation, including the theoretical method and basis-set, are carefully determined. To eliminate the drawbacks of the DM formula, a modified DM formula is set in this paper. The modified DM formula, of which the weighting factors are changed, has a better agreement with the experimental data on both the peak and shape of the cross-section curves. The results calculated by DM formula and modified DM formula are given as references to fill in gaps in further research into C5 F10 O and C4 F7 N.